The Multipronged Approach of Solid Waste Management Toward Zero Waste to Landfill Site: An Indonesia and Thailand Experience - Ariva Sugandi Permana; Sholihin As’ad; Chantamon Potipituk (My University, 2023)
Abstract The zero-waste term in municipal solid waste management has been the utopian objective of every waste management authority in the cities in developing countries, even though it comes with different perceptions, which are sometimes misguided. People can produce no waste unless they live with no consumption. The zero-waste term does not mean that we produce no waste, rather we dump no waste at the landfill site. It means we dispose of nothing at a landfill site since the issue of landfill site can be a culprit of waste management, for its reiterating city land demands that generate “headaches” to city authority because of NIMBYism (Not In My Back Yard issue). No one accepts living voluntarily next to a landfill site as it creates more harm than harmless. With zero waste at the landfill site in mind, the waste management authority attempts to deal with the complexity of municipal solid waste management, by reviving each element of the waste management stakeholders to concertedly move on to deal with waste. Individual households and communities, without which waste management will not be successful, were positioned as the main thrust of waste management. A multipronged approach was implemented with all stakeholders, i.e., lawmakers, regulators, waste producers, implementers, and pressure groups, appearing with different functions but a common point: zero waste at the landfill site. A stakeholder with a large capacity, i.e., local government focuses on creating a large project that has a large impact on overall waste management; private sectors may contribute to establishing recycling centers, and waste-to-energy projects. Meanwhile, the individual households, which are large in number but have a small capacity, establish community-based activities, i.e., waste banks. This chapter attempts to provide the overall picture of municipal solid waste management in 14 cities in developing countries toward their goal of zero waste at landfill sites.
Keywords: Municipal Solid Waste Management; Recycling and Waste Management Techniques; Healthcare and Environmental Waste Management